EXAM REF PL-900 MICROSOFT POWER PLATFORM FUNDAMENTALS - Zacker, Craig (MICROSOFT, 2023)
Prepare for Microsoft Exam PL-900. Demonstrate your real-world knowledge of the fundamentals of Microsoft Power Platform, including its business value, core components, and the capabilities and advantages of Power BI, Power Apps, Power Automate, and Power Virtual Agents. Designed for business users, functional consultants, and other professionals, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified: Power Platform Fundamentals level.